Association of leptin levels with pathogenetic risk of coronary heart disease and stroke: a meta-analysis - Zeng,Rui (2014)
Objective This meta-analysis aimed to investigate the association of leptin levels with pathogenetic risk of CHD and stroke. Materials and methods Studies were identified in the PubMed, Embase, and Springer link database without language restriction. Odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs) were used as effect indexes. The association of leptin levels with pathogenetic risk of CHD and stroke, as well as the risk variation of CHD with each additional one unit of leptin level were examined via meta-analysis. The publication bias was assessed via Egger’s linear regression test. Results Eight nested case-control studies consisting of 1,980 patients and 11,567 controls were included for current meta-analysis. ORs (95% CIs) of association of leptin levels with CHD and stroke was 1.90 (1.06, 3.43), and 2.14 (1.48, 3.08), respectively. In addition, significant result was obtained regarding the risk variation of CHD with each additional one unit of leptin level (OR =1.04, 95% CI =1.00‐1.08, P=0.044). There was no significant publication bias as suggested by Egger test outcomes. Conclusion There was a significant association of leptin with pathogenetic risk of CHD and stroke, and raised leptin levels could significantly increase the pathogenetic risk of CHD.